Analisis Strategi Pemasaran Kopi dalam Meningkatkan Volume Penjualan di PT. Utokopia Coffee Surabaya - Asnanda Fairuz Tsuraya; Acep Samsudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the marketing strategies implemented by PT. Utokopia Coffee Surabaya in increasing sales volume amid the increasingly competitive coffee business. The research method used is qualitative with a descriptive approach, which includes in-depth interviews, observations, and document analysis. The results show that Utokopia Coffee has strengths in product quality and strategic location, but also faces weaknesses in promotion and seating capacity. Opportunities for growth exist in the increasing coffee consumption trend, while threats come from intense competition. By applying SWOT analysis, this study recommends improving facilities, innovating the menu, and adopting more interactive marketing strategies to enhance competitiveness and sales volume.